Case on Quality Engineering: Acceptance Sampling - Zubair, Khalil (Penerbit UMP, 2017)
Acceptance sampling is an inspection method that are widely use in vast area of industrial application and implementations to inspect a large numbers of items in a short amount of time without decreasing the quality of the items or inspection precision. It is ideal to inspect all the product manufactured in factory line to ensure the quality of the product without nonconformities (unacceptable product quality) but it is almost impossible to inspect every product without consuming very long period of time, labor costs and possibly causing human error because of fatigue and boredom that will reversely make the nonconform product miss the inspection. The method is very useful in the inspection of for example, food [2], computation [3], geo-science [4], production [5] etc.